URDU: عصر حاضر میں اسلام کے تصور ولایت کی اہمیت و ضرورت: The importance and need of Guardianship in Islam in contemporary time - Atiq, Dr. Ambreen; Dr. Abu Sufyan Qazi Furqan Ahmad; Dr. Khawaja Saif ur Rehman (Rahat-ul-Quloob, 2021)
According to Islamic Jurisprudence, one of the most important requirements for a sound marriage is the total agreement of the woman under the guardianship of her father or any other mahram relative. In case of none, the ruler or the judge assume to be a guardian or Wali of a woman. A guardian or Wali is responsible for the selection of the righteous person for the woman and assures the protection and welfare of her Rights and interests. He has the authority to reject and refuse the proposal if the suitor did not deem a sound and sincere match. A marriage without a guardian is considered unlawful, as there is no concept of love affairs and courtship without a guardian in Islam. The guardian evaluates the religious, social and economic compatibility of the couple, while on the other hand a woman selects the spouse on physical attraction and romantic notion which vanishes out soon as the real life starts causing potential problems in relationship. That why Islam lays down principle and law of wilayat for a lady to protect her interests and rights and consider to be a shield and safeguard for her welfare in future marital life.